Review on Shadbindu Ghritha –a Sneha Kalpana - Nanda; M.S.Doddamani (International Journal of Pharmacy and Analytical Research, 2022)
Ghritas are preparations in which ghee is boiled with prescribed kashaya(decoction) and kalka of drugs according to the formula. This process ensures absorption of the active therapeutic principles of the ingredients used. Generally the proportion is one part of Kalka, four parts of ghritha, sixteen parts of dravadravya .Shadbindu ghritha is one of the Snehakalpana, two different references are available in classics in vangasenasamhitha and yogaratnakara.It contains ingredients like Bhringaraja (Eclipta alba),Yashtimadhu(Glycyrrhizaglabra),Kushta(saussurealappa),Lavanga (syziumaromaticum),Shunti (zingiberofficinale),Vidanga (Embliaribes) is replaced by kushta and vice versa.